2004
DOI: 10.1002/app.20990
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of carbon/epoxy composites

Abstract: ABSTRACT:The recycling of carbon fibers from carbon/ epoxy composites was attempted with a solvent method in nitric acid solutions. Gel permeation chromatography and gas chromatography/mass spectrometry showed that the epoxy resin could entirely decompose into low-molecularweight compounds, and the main components of the dissoluble decomposed compounds were 2,4-dinitrophenol and 2-nitro-4-carboxylphenol. Electron probe microscopy showed no damage to the recycled carbon fibers. The singlefiber tension strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(66 citation statements)
references
References 6 publications
0
66
0
Order By: Relevance
“…According to the statistics, the world-wide demand for carbon fibers reached approximately 35,000 tons in 2008 and this number is expected to double in 2014, indicating a growth rate of over 12% per year [5]. The increasing requirement of carbon fiber has raised an environmental and economic awareness among researchers for the need to recycle the CFRP waste material in a suitable way [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to the statistics, the world-wide demand for carbon fibers reached approximately 35,000 tons in 2008 and this number is expected to double in 2014, indicating a growth rate of over 12% per year [5]. The increasing requirement of carbon fiber has raised an environmental and economic awareness among researchers for the need to recycle the CFRP waste material in a suitable way [10].…”
Section: Introductionmentioning
confidence: 99%
“…The recovery of CF from the composite material has been attempted using a range of processes, including chemical, mechanical, thermal, and even its use as a fuel after incineration has been investigated. Liu et al 1 reported a thermochemical method for recycling of CF filled epoxy composites from rocket engine shells. Optimum recovery of CF was obtained, with no damage to the fibers, using an 8M nitric acid solution and a decomposition temperature of 908C for a 4% nitric acid solution.…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al [10] used a pyrolysis process to recover glass fibres and volatile materials from different composites. Liu et al [11] used nitric acid to recover carbon fibres from epoxy resin/carbon fibre composite at 90 • C. Meng et al [12] used supercritical water to recycle carbon fibre composites.…”
Section: Introductionmentioning
confidence: 99%